A Metaphor to Build Empires: Imitatio and the Politics of Representation in European Humanism (The International Journal of Educational Sciences and Arts, 2024)
In Western criticism and philosophy, Renaissance discussions of imitation have often been seen as both a legacy of Greece and Rome, and as the foundation of modern theories of art and literature. This investigation shows that the discussions of imitation that spread throughout the Renaissance were indeed adopted from Latin Roman discussions of poetry and rhetoric, but they have no connection to the famous Greek philosophical concepts of mimesis/imitation that are found in the work of Plato and Aristotle. Indeed, European concepts of imitatio/ imitation, as this study shows, developed their conceptual potential before Plato’s and Aristotle’s discussions of mimesis became familiar in Europe. Furthermore, Renaissance discussions of imitation were not theories of art and literature, as is commonly believed. They were simply an educational pedagogy that organized the appropriation of the canons of description of classical Latin into the vernaculars. The peculiarity and the scale of this pedagogy become evident when located within its geopolitical context. In the early modern era, neither the dead Latin language nor the vernaculars were equipped to manage the wealth or the administrative and cultural needs of ascending European states. Like Rome at the height of its power, European states were emerging empires in need of a language and a culture. And just like the Romans resorted to the imitation of Greek masterpieces in order to develop their language, Europeans advocated the imitation of Latin masterpieces to develop their vernaculars. But while the Romans resorted to imitatio often with resentment and bitterness at the impossibility to match the Greek achievement, European humanists considered imitatio to have been a resounding success [sic]. By adopting the Roman practice of imitatio, European cultures appropriated and internalized Roman ambivalence without solving or even identifying it.
Keywords: Imitatio; Imitation in the Renaissance; Poetry and Humanist Education; Literature and Empire; Renaissance Literature and the Classics; Renaissance Criticism